Modelling Of Mechanical Behaviour Of Electronics Materials - Fun, Seng Phan (Universiti Sains Malaysia, 2019)
Lead free solder Sn-Ag-Cu is investigated and studied to replace the leaded solder after the usage of lead components has been limited by Europe Union through the Restriction of Hazardous Substance (RoHS). Due to constant push on miniaturization in electronic package, strength of solder joint of electronic component on circuit board is reduced due to decrease in contact area. Therefore, the strength of the solder joint is very important in every aspect especially in miniaturization of electronic components and systems driven by the demand of people to reduce the size and weight of electronic devices. Thus, it is vital to study and understand various material properties of the lead free solder and nanoparticles reinforced solder. These material properties include the Young’s Modulus, hardness, yield strength and tangent modulus of the solder. Nanoindentation technique and finite element analysis provides an approach to characterize these elastic-plastic behavior of the lead free solder. By using surface mounting technology, miniaturized capacitors are placed on printed solder paste on printed circuit board and undergo reflow soldering. Then, the samples are prepared in cold mounted sectioned printed circuit board. The mechanical characteristic is measured by using nanoindentation experiment to determine the elastic modulus and hardness of SAC 305 and nanoparticles reinforced lead free solder. Besides, the yield strength and tangent modulus of SAC 305 is determined by using simulation in ANSYS by curve fitting of the load displacement graph of experiment and simulation. In conclusion, the addition of nanoparticles in SAC 305 does not show much improvement in properties of the solder. The yield strength and tangent modulus for SAC 305 are 68MPa and 180MPa respectively.